A novel therapy to promote axonal fusion in human digital nerves. (November 2016) - Bamba, Ravinder; Waitayawinyu, Thanapong; Nookala, Ratnam; Riley, David Colton; Boyer, Richard B.; Sexton, Kevin W.; Boonyasirikool, Chinnakart; Niempoog, Sunyarn; Kelm, Nathaniel D.; Does, Mark D.; Dortch, Richard D.; Shack, Robert Bruce; et al.
Abstract : BACKGROUND: Peripheral nerve injury can have a devastating impact on our military and veteran population. Current strategies for peripheral nerve repair include techniques such as nerve tubes, nerve grafts, tissue matrices, and nerve growth guides to enhance the number of regenerating axons. Even with such advanced techniques, it takes months to regain function. In animal models, polyethylene glycol (PEG) therapy has shown to improve both physiologic and behavioral outcomes after nerve transection by fusion of a portion of the proximal axons to the distal axon stumps. The objective of this study was to show the efficacy of PEG fusion in humans and to retrospectively compare PEG fusion to standard nerve repair. METHODS: Patients with traumatic lacerations involving digital nerves were treated with PEG after standard microsurgical neurorrhaphy. Sensory assessment after injury was performed at 1 week, 2 weeks, 1 month, and 2 months using static two-point discrimination and Semmes-Weinstein monofilament testing. The Medical Research Council Classification (MRCC) for Sensory Recovery Scale was used to evaluate the level of injury. The PEG fusion group was compared to patient-matched controls whose data were retrospectively collected. RESULTS: Four PEG fusions were performed on four nerve transections in two patients. Polyethylene glycol therapy improves functional outcomes and speed of nerve recovery in clinical setting assessed by average MRCC score in week 1 (2.8 vs 1.0, p = 0.03). At 4 weeks, MRCC remained superior in the PEG fusion group (3.8 vs 1.3, p = 0.01). At 8 weeks, there was improvement in both groups with the PEG fusion cohort remaining statistically better (4.0 vs 1.7, p = 0.01). CONCLUSION: Polyethylene glycol fusion is a novel therapy for peripheral nerve repair with proven effectiveness in animal models. Clinical studies are still in early stages but have had encouraging results. Polyethylene glycol fusion is a potential revolutionary therapy in peripheral nerve repair but needs further investigation. LEVEL OF EVIDENCE: Therapeutic study, level IV. Abstract : Supplemental digital content is available in the text.